Analysis of dependency of ice-cloud on cloud base temperature with the polarized micro-pulse lidar over Ny-Alesund - Kyohei, Yamada; Masataka, Shiobara; Yutaka, Kondo (2016)
第7回極域科学シンポジウム:[OM] 極域気水圏 11月29日（火）国立極地研究所 2階 大会議室 conference object